Do narcissistic CEOs rock the boat?. (17th April 2020) - Aabo, Tom; Hoejland, Frederik; Pedersen, Jesper
Abstract : Purpose: The purpose of this paper is to investigate the role of narcissistic supply for the association between CEO narcissism and corporate risk taking. Design/methodology/approach: The authors investigate a sample of 281 non-financial S&P 1500 firms and a corresponding 457 CEOs in the 10-yr period 2006–2015. Findings: The association between CEO narcissism and corporate risk taking depends on the admiration, attention, and affirmation of own superiority ("narcissistic supply") that the CEO receives given her/his current position. Thus, a narcissistic CEO with an insufficient narcissistic supply (small firm/small compensation) will crave for more and take more risks ("rock the boat") while a narcissistic CEO with a sufficient narcissistic supply (large firm/large compensation) will protect the status quo and be reluctant to take new risks. Specifically, the authors find that a change from a slightly narcissistic CEO to a strongly narcissistic CEO, for positions entailing limited (abundant) narcissistic supply, is associated with an increase (a decrease) in corporate risk of 6%–8% (11%–27%). Originality/value: Previous research indicates a positive association between CEO narcissism and corporate risk taking in specific domains such as M&A and R&D activities. This paper provides a novel contribution to the existing literature by identifying and assessing the important role of narcissistic supply for the association between CEO narcissism and corporate risk taking in general.